Methods of control for minimizing extra-fine needle deflection with a combination of vibration and rotation in the lower abdomen - Ryosuke TSUMURA; Hiroyasu IWATA (Journal of Biomechanical Science and Engineering, 2017)
Cancer vaccine therapy is a novel treatment method which uses an extra-fine (0.53 mm in diameter (25 G)) needle to deliver a tumor-specific vaccine directly into a tumor. This method is expected to deliver an effective treatment with few side effects. However, the procedure is very difficult to perform because of needle deflection. We intend to develop a needle insertion robot to combat this deflection and deliver the vaccine successfully. The key features of the robot were developed to minimize needle tip deflection while traversing complex tissues which is composed of various tissues. In this paper, as targeted to lower abdomen, we propose a control method for minimizing needle tip deflection during insertion through vibration and axial rotation. The effectiveness of the proposed method was evaluated in artificial and biomaterial tissues found in the lower abdomen (muscle, bowel, and skin). Results demonstrated that the effectiveness of vibration and rotation was changed depending on the kind of the tissues. The rotation was effective to the thick tissues (muscle and skin) and the vibration was effective to membranous tissues (bowel). Based on the results, our method used vibration and rotation when the needle is inserted into the skin and muscle and only vibration when traversing through soft tissue such as the bowel. In conclusion, the proposed method can minimize needle tip deflection robustly in a lower abdomen phantom.